EKSTRAKSI BAHAN HUMAT DARI BATUBARA (SUBBITUMINUS) DENGAN MENGGUNAKAN 10 JENIS PELARUT - Dewi Rezki; Fachri Ahmad; Gusnidar Gusnidar (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2007)
This experiment was conducted to extract sub-bituminous coals for obtaining humic substances by using 10 kinds of extract solutions. The best and effective solution was investigated and also the characteristics of humic substances soluble in those solution. Complete Randomize Design was used to find out the effect of treatments. Two types of coals were taken from Pasaman and Sawahlunto and the ten kinds of extract solutions were 0.1 N NaOH, 0.5 N NaOH, 0.1 M Na2CO3, 0.5 Na2CO3, 0.1 N HCl, 0.1 M Formic Acid, 0.1 M Oxalic Acid, 0.025 N HF, Ethanol 70 %, and Ethanol 90 %. Results of this laboratory experiment showed that all ten extraction solutions had the ability to extract humic substances but in different amount. The best solution that could be used effectively was 0.5 N NaOH. This solution could extract 31.5 % of humic substances from Pasaman Sub-bituminous coals, but only 15.4 % could be extracted from that of Sawahlunto. Infra Red Spectrometer was also used to identify the characteristics of functional groups appear on those humic substances extracted.Key Words: humic acid, coal